Enhancing Teachers' Digital Pedagogical Skills Through Canva-Based Interactive Media Development: Evidence from Elementary School Educators - Mega Adyna Movitaria; Edriagus Saputra; Melda Delvia; Wisda Rahmadinur (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2026)
The purpose of this community service is to provide insight into Canva to teachers so that there is an increase in the design, presentation, and creativity skills of educators. If teachers are able to use this Canva learning media, it will make it easier for teachers to deliver material in learning. The method of implementing the service uses a participatory workshop approach, which includes material presentations, discussions, and questions and answers, direct practice of making learning media, and microteaching as an initial form of application. The results of this community service activity are to improve teachers' skills in using digital media, especially Canva, creatively, communicatively, and collaboratively in the learning process. Through a direct practice approach, teachers are able to produce interactive and relevant learning media with Islamic Religious Education material, while developing soft skills such as creativity, technology adaptation, and cooperation. The contribution of the results of these service activities not only has an impact on improving individual teacher competencies but also supports the development of innovative learning practices and strengthens the capacity of the teacher community in facing the transformation of digital education in a sustainable manner.